Honduran nurses’ perceptions among the quality of care for stroke patients: a qualitative study - Sandra Patricia Nájera Figueroa; Oscar Fidel Antunez Martinez; Perla Simons Morales (Revista Latino-Americana de Enfermagem, 2025)
Objective: to explore the nurses’ perceptions among the quality of care to stroke patients in a public hospital in Northern Honduras. Method: a descriptive phenomenological study was carried out. The data collection was conducted by means of depth- interviews to 20 general nurses from the emergency and clinical medicine departments from the Atlántida General Hospital. Data analysis was by thematic technique. Results: the research found three key themes, and 10 subthemes, which illustrated the quality of stroke patients care in a general hospital from Honduras. The finding points up the theme “negative outcomes regarding the structure dimension of the patient care units”, which means the failure to improve or maintain the quality of healthcare. Likewise, “positive outcomes regarding the nursing process”, defined as pleasant and helpful among the care of stroke patients, such as ethical and humanized caring, and activities on promoting patient self-care with involvement of the relatives. Conclusion: the results indicate that Honduran nurses do not have qualified graduate training in critical care, which is a limitation that compromises the quality of care. Therefore, it is recommended to have clear organization structures and better resources managing, consequently, it may increase user satisfaction, as well as reducing hospital stays.